High undescribed diversity of Amanita section Vaginatae in northern Thailand - B. Thongbai (2018)
© Guizhou Academy of Agricultural Sciences. Amanita sect. Vaginatae is the most speciose section of Amanita subg. Amanita. However, to date only three species belonging to this section have been reported from northern Thailand. Here, we report on the study of Amanita sect. Vaginatae specimens collected in the years of 2012 to 2016. Remarkably, all fifteen specimens studied belong to nine species new to science, which were identified based on morphology and DNA sequence analyses of β-tubulin, nrLSU, nrITS, and rpb2 gene. Those nine species are fully described and illustrated with line drawings and color photographs. Morphological characteristics of related taxa are compared and discussed, and a dichotomous key of Amanita sect. Vaginatae in Thailand is provided.